Determinants of Diarrhea Disease Environmental Conditions in Manutapen Village Kupang City - Byantarsih Widyaningrum; Christine J K Ekawati (JOURNAL of HEALTH SCIENCE REVIEW, 2024)
One of the environmental-based diseases that is still often found in developing countries is diarrheal disease. Diarrhea can also cause death. Limited toilet facilities in Manutapen Village, Kupang City could be one of the causes of the high number of diarrhea cases in the area. This type of research is descriptive with a survey method. Cross sectional sampling. The data taken is primary and secondary data. The results of the study showed that as many as 87.10% of diarrhea sufferers were > 5 years old, the distance is cubluk / resapans in toilets for diarrhea sufferers < 10 meters from the well are 12.90%, condition of toilet floors in houses of diarrhea sufferers that are not tight is 74.20%, condition of dirt/feces entry holes in open latrines is 6.45%, length / The width of the latrine floor in the house of diarrhea sufferers which is < 1 meter is 67.74%, the latrine house of diarrhea sufferers which does not have a roof is 19.35%. The conclusions that can be drawn are the distance of the cesspool to the source of clean water, the condition of the latrine floor, the condition of the dirt entry hole, the size of the floor area and the condition of the latrine house which does not meet health requirements can be factors that cause diarrhea